KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS V PADA MATERI OPERASI HITUNG PECAHAN - Khoirotun Nissa, Nabillah Nur; Feny Rita Fiantika; Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the numeracy literacy skills of fifth grade elementary school students in solving fractional arithmetic operations problems. Numeracy literacy, which involves understanding, using, and applying mathematical concepts in the context of everyday life, is the main focus of this study. The subjects of the study consisted of three students with high, medium, and low levels of numeracy literacy skills, selected through a case study at SDN Tenggilis Mejoyo 1 Surabaya. The method used was descriptive qualitative, with data collection through numeracy literacy tests and interviews. The results of the study showed variations in abilities among students, where most were able to apply numeracy literacy in everyday life, while others still had difficulties. Based on these findings, the study suggests that mathematics learning be applied contextually and use interesting media to improve understanding of fraction concepts, as well as optimizing collaboration between teachers and parents in improving students' numeracy literacy.